Immune responses of ducks infected with duck Tembusu virus - Li, Ning; Wang, Yao; Li, Rong; Liu, Jiyuan; Zhang, Jinzhou; Cai, Yumei; Liu, Sidang; Chai, Tongjie; Wei, Liangmeng (Frontiers in Microbiology, 2015)
Duck Tembusu virus (DTMUV) can cause serious disease in ducks, characterized by reduced egg production. Although the virus has been isolated and detection methods developed, the host immune responses to DTMUV infection are unclear. Therefore, we systematically examined the expression of immune-related genes and the viral distribution in DTMUV-infected ducks, using quantitative real-time PCR. Our results show that DTMUV replicates quickly in many tissues early in infection, with the highest viral titers in the spleen 1 day after infection. Rig-1, Mda5, and Tlr3 are involved in the host immune response to DTMUV, and the expression of proinflammatory cytokines (Il-1β, -2, -6, Cxcl8) and antiviral proteins (Mx, Oas, etc.) are also upregulated early in infection. The expression of Il-6 increased most significantly in the tissues tested. The upregulation of Mhc-I was observed in the brain and spleen, but the expression of Mhc-II was upregulated in the brain and downregulated in the spleen. The expression of the interferons was also upregulated to different degrees in the spleen but that of the brain was various. Our study suggests that DTMUV replicates rapidly in various tissues and that the host immune responses are activated early in infection. However, the overexpression of cytokines may damage the host. These results extend our understanding of the immune responses of ducks to DTMUV infection, and provide insight into the pathogenesis of DTMUV attributable to host factors.